The Use of Sketching Technique to Help Deaf Children in Bahasa Melayu Essay’s Report - Nurul Addina Rashid; Mohd Hanafi Mohd Yasin (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Deaf children usually face language difficulties which affect their writing skills. This qualitative research is conducted to introduce a sketching method that will improve children’s skills in writing Report in Bahasa Melayu. Scaffolding technique from Wood, Bruner and Ross is applied to lead deaf children in mastering writing technique proportionally. This experimental research involves 8 deaf students which are divided into two groups, namely experimental group and control group. Sample’s knowledge, personal experience and education level have been taken into consideration in the sampling technique. Pre-test Instrument, Post-test and semi-structured interview are used to measure the efficiency of this technique. Experimental group received writing intervention, guided by sketching of the essay structure in two phases, which are sketching phase and drawing and writing phase. Essays written during Intervention B are assessed based on the marking rubric prepared. The data is described descriptively to answer research questions. External validity depends on the ability of writing technique as a responding variable, affecting the manipulated variable, which is student’s writing ability. The findings in pre-test and post-test are compared. It is found that the mean of experimental group is higher, which is 8.5 compared to mean of control group, which is 0.5 after the intervention phase. When interviewed, all samples from the experimental group are interested to continue using this technique after the experiment. It is concluded that sketching technique is effective in helping deaf students to write a Malay language report.